Group Counseling Reality with Confrontation Techniques to Improve Self-Control and Self-Perception Students Problematic Internet Use (Universitas Negeri Semarang, 2019)
This study aims to examine the effectiveness of reality group counseling confrontation techniques for students with self-control and low self-perception with the tendency of problematic internet use behavior. This study uses Manova design involving 14 students. The technique of analyzing data used is Manova. The statistical results show that reality of group counseling has been shown to be effective in improving self-control and low self-perception. This finding proves that the counseling of reality groups is an effective confrontation technique to improve self-control and self-perception in problematic internet use students.